Behavioral Determinants of Handwashing with Soap Among Mothers and Caretakers : Emergent Learning from Senegal and Peru - World Bank (Washington, DC, 2012)
The Water and Sanitation Program (WSP) has supported the Global Scaling up Handwashing Project in Peru, Senegal, Tanzania, and Vietnam. The project has tested whether innovative promotional approaches to behavior change can generate widespread and sustained improvements in household hygiene practices. The implementation phase of the project ended in June 2011. The project has a significant learning objective, an important component of which is to ascertain the key factors that influence behavior change. These are known as behavioral determinants. Studies such as a formative research study conducted in Kenya in 2007 have found that while knowledge around hand-washing tends to be high, practice rates are low. This finding is illustrative of the knowledge-behavior gap encountered by anti-smoking and condom-use initiatives, among others, and reflects the complexity of human behavior. More specifically, FOAM (Focus, Opportunity, Ability, and Motivation) was developed to inform the design of formative research, interventions as well as monitoring to increase the effectiveness of its behavior change program. A key feature of the project is its monitoring and evaluation component, which includes randomized control baseline and end-line studies, longitudinal surveys, periodic implementation surveys, and a comprehensive management information system (MIS) that enabled continuous monitoring and improvement. These components have been used to measure and track key indicators such as diarrhea incidence. This Learning Note aims to highlight key findings from two studies, the impact evaluation baseline study conducted in Peru in 20074 and a 'doer/non-doer' study conducted in Senegal in 2010.